SISTEM PENYIRAMAN DAN PEMUPUKAN OTOMATIS BERBASIS INTERNET OF THINGS (IOT) DENGAN PEMANTAUAN ANTARMUKA APLIKASI ANDROID - Wiranto, Wiranto; Musyrifah, Musyrifah; Mansyur, Muh Fuad (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
Technological developments in the field of agriculture are now expanding widely, various modern tools must be owned to assist farmers in cultivating plants. The owners of the chili plants do watering and fertilizing by collecting water or fertilizer and then giving it to the plants one by one. This is not a problem if the plant owner has free time. However, if the plant owner is busy with other things or is having business that makes the plant owner unable to care for the plant, then this becomes a problem because when the plant does not receive sufficient care, the plant will easily wither and die. Seeing the existing problems, this research will design a system that can automatically water and fertilize plants based on IoT with monitoring from an Android application. The design of this system uses an Arduino microcontroller as a controller, the nodeMCU esp2688 wifi module to send data from the sensor to the web server, a soil moisture sensor to determine soil moisture, a real time clock (RTC) for fertilization scheduling and a relay as an automatic switch on the water pump. This system aims to help the activities of farmers who still use physical force to water and fertilize plants. The IoT-based automatic watering and fertilizing system uses the prototype development method, namely by collecting system requirements, building prototyping, evaluating prototyping, coding the system, testing the system, evaluating the system and using the system